CAP Reform and Price Transmission in the Italian Pasta Chain. Issue 4 (4th March 2016) - Cacchiarelli, Luca; Lass, Daniel; Sorrentino, Alessandro
ABSTRACT: During the last several years, wheat‐pasta chains have been affected by Common Agricultural Policy (CAP) reforms in the durum wheat sector that have progressively reduced government intervention in the market. Specifically, the mid‐term reform, implemented in 2005, represented a deep change in the tools applied in the CAP, with a change from coupled income support to a single decoupled aid where farmers' incomes are directly supported and are no longer linked to levels or types of production. We hypothesize that price transmission along the wheat‐pasta supply chain has been affected by CAP reform and other events through greater price volatility for durum wheat and market power exerted by some firms along the supply chain. For the present study, we are particularly interested in examining whether and how CAP reform has altered price transmission in the Italian wheat‐pasta chain, from farmer to retailer, including the wholesale stage. We employ the Kinnucan and Forker model, which provides a convenient instrument for analyzing the impact of policy intervention, and adapted its structure to the characteristics and the composition of the pasta supply chain by introducing an intermediate level (wholesale price), represented by semolina producers. The results suggest that pricing behavior has changed after CAP Reform introduction. [EconLit citations: Q110; Q130; L110].